Does the choice of mobile C-arms lead to a reduction of the intraoperative radiation dose?. Issue 8 (August 2016) - Richter, P.H.; Steinbrener, J.; Schicho, A.; Gebhard, F.
Abstract: Introduction: Mobile C-arm imaging is commonly used in operating rooms worldwide. Especially in orthopaedic surgery, intraoperative C-arms are used on a daily basis. Because of new minimally-invasive surgical procedures a development in intraoperative imaging is required. The purpose of this article is investigate if the choice of mobile C-arms with flat panel detector technology (Siemens Cios Alpha and Ziehm Vision RFD) influences image quality and dose using standard, commercially available test devices. Materials and methods: For a total of four clinical application settings, two zoom formats, and all dose levels provided, the transmission dose was measured and representative images were recorded for each test device. The data was scored by four observers to assess low contrast and spatial resolution performance. The results were converted to a relative image quality figure allowing for a direct image quality and dose comparison of the two systems. Results: For one test device, the Cios Alpha system achieved equivalent (within the inter-observer standard error) or better low contrast resolution scores at significantly lower dose levels, while the results of the other test device suggested that both systems achieved similar image quality at the same dose. The Cios Alpha system achieved equivalent or better spatial resolution at significantly lower dose for all application settings except for Cardiac, where a comparable spatial resolution was achieved at the same dose. Conclusion: The correct choice of a mobile C-arm is very important, because it can lead to a reduction of the intraoperative radiation dose without negative effects on image quality. This can be a big advantage to reduce intraoperative radiation not only for the patient but also for the entire OR-team.